IMPLEMENTASI PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS MEDIA KARTUN ISLAMI DALAM MEMBINA AKHLAK SISWA DI SEKOLAH DASAR - Neng Nurcahyati Sinulingga (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2022)
The presence of interesting learning media, of course, greatly affects the cognitive development of students, especially in audiovisual learning such as animated appearances filled with characters who can teach educational messages as well as morals and religion. Therefore, one of the learning media that can be used for elementary school students is by presenting PAI learning media by displaying Islamic cartoon-based learning that can be accessed in various applications via the internet and also videos that can be accessed via youtube . This study aims to develop students' insight, as well as identify the values of Islamic education contained in the children's Islamic cartoon series. This research is classified as a literature review research, which is based on accurate references and references, and is analyzed interactively. religious values based on Islamic teachings, and this also makes Islamic cartoons a reference for teachers to always develop learning media, because the science and knowledge in this cartoon series has represented a picture of their daily activities which are of course carried out in accordance with the teachings Islam.